Efforts to Improve Bank Marketing Performance - Paulus Wardoyo; Endang Rusdianti (Fakultas Ekonomi, Universitas Bangka Belitung, 2019)
This study aims to build and analyze research models that can be used to improve bank marketing performance. The population is 165 people, while the sampling technique used is purposive sampling and a sample of 135 respondents was obtained. This study uses four variables, namely satisfaction, customer retention, internet banking service quality, and marketing performance. Descriptive analysis was carried out using index numbers, completion of inferential statistics was carried out with the help of Smart software PLS version 2.0. The four hypotheses used in this study were all accepted. To improve marketing performance, management must first be able to build good relationships with its customers. Relationships must be long-term oriented and mutually beneficial.